Evolving the Concept of Default in Relation to Losses Arising from Standard Agreements for Bank Account Openings - Sulaiman, Sepriyadi Adhan; Emirzon, Joni; Hamzah, Hamzah (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
This research examines the legal responsibility of banks as commercial service providers, which is primarily based on contractual obligations with consumers. While the foundation for customer claims against banks typically arises from breaches of these agreements, the Consumer Protection Law does not explicitly outline various forms of responsibility, resulting in numerous decisions by the Consumer Dispute Settlement Body being overturned by the Supreme Court. One significant issue is the law’s lack of provision for legal claims beyond tort. Using a normative methodology based on Law Number 8 of 1999 on Consumer Protection, this study underscores the need for a legal framework that emphasizes risk-based bank responsibility for losses stemming from standard agreements in opening bank accounts. This development is essential for strengthening consumer protection and achieving a balance between consumer interests and the rights of business actors, thereby promoting a healthier economic environment.